Kelinci Pemeliharaan secara ilmiah, tepat dan terpadu Faiz Manshur; editor, Mathori A. Elwa, Siti Nur Aryani - MANSHUR, Faiz; Elwa, Mathori A.; Aryani, Siti Nur (Nuansa, 2009)
283 hlm. : ilus. ; 24 cm. [ 2 eks ]